Towards the discovery of boiler physics in a Kraft recovery boiler using sparse identification of non-linear dynamics - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2022)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2021.